Electrochemical device and electronic device
By setting a glue layer on the isolation membrane of the lithium-ion battery away from the center surface of the electrode assembly and bonding to the shell, the safety hazards of the lithium-ion battery during drop or impact are solved, the safety is improved and the stability of the energy density is maintained. .
Patent Information
- Application Number
- CN202411363210.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2021-03-31
- Publication Date
- 2024-12-17
AI Technical Summary
When a lithium-ion battery falls or impacts, there is a safety hazard due to the lack of adhesiveness between the housing and the electrode assembly, and increasing the adhesive material will affect the energy density.
The isolation film of the electrode assembly is arranged away from the central surface of the electrode assembly, so that the end of the isolation film extends out and bonds to the shell, ensuring that the bonding area between the adhesive layer and the shell reaches at least the contact area between the shell and the electrode assembly. 10%, and excellent bonding properties are formed through polymer polymer.
Improves the safety of lithium-ion batteries, avoids structural damage caused by drops or impacts, and minimizes the impact on energy density.
Smart Images

Figure CN119153815A_ABST
Abstract
Description
[0001] This application is a divisional application with application number 202180001889.3, application date March 31, 2021, and invention name “An electrochemical device and an electronic device”. Technical Field
[0002] The present application relates to the field of electrochemical technology, and in particular to an electrochemical device and an electronic device. Background Art
[0003] Lithium-ion batteries (electrochemical devices) have the characteristics of large specific energy, high operating voltage, low self-discharge rate, small size and light weight. They are widely used in various fields such as energy storage, portable electronic devices and electric vehicles. As the scope of use of lithium-ion batteries continues to expand, the market has put forward higher requirements for lithium-ion batteries, requiring lithium-ion batteries to have higher energy density and better safety. During the use of lithium-ion batteries, it is inevitable that there will be problems such as falling and collision. It is particularly important to improve the safety of lithium-ion batteries in the event of abuse such as falling and collision.
[0004] There is usually no adhesion between the shell and the electrode assembly of a lithium-ion battery, which leads to relative displacement between the electrode assembly and the shell when the lithium-ion battery is dropped, hit, or otherwise abused, resulting in safety hazards. Therefore, a new technical solution is urgently needed that can improve the safety performance of lithium-ion batteries while reducing the impact on the energy density of lithium-ion batteries. Summary of the invention
[0005] The purpose of this application is to provide an electrochemical device and an electronic device to improve the safety performance of the electrochemical device and reduce the impact on the energy density of the electrochemical device. The specific technical solution is as follows:
[0006] It should be noted that in the following content of the present application, the present application is explained by taking a lithium ion battery as an example of an electrochemical device, but the electrochemical device of the present application is not limited to a lithium ion battery.
[0007] The specific technical solutions are as follows:
[0008] The first aspect of the present application provides an electrochemical device, which includes a shell and a wound electrode assembly disposed in the shell, wherein the electrode assembly includes a first pole piece, a second pole piece with a polarity opposite to that of the first pole piece, a first isolation film or a second isolation film is disposed between the first pole piece and the second pole piece, and the first pole piece includes a first current collector. Among them, a first adhesive layer is disposed on the surface of the first isolation film and / or the second isolation film away from the center of the electrode assembly, the first isolation film and / or the second isolation film extends from the tail end of the electrode assembly and is bonded to the shell through the first adhesive layer, and the area bonded to the shell by the first adhesive layer is greater than or equal to 10% of the contact area between the shell and the electrode assembly.
[0009] In the present application, a first isolation film or a second isolation film is arranged between the first pole piece and the second pole piece, that is, the first isolation film and the second isolation film can be alternately arranged between the first pole piece and the second pole piece. The present application has no particular restrictions on the specific arrangement method, as long as the requirements of the present application are met. Exemplarily, the electrode assembly can be formed by stacking the first pole piece, the first isolation film, the second pole piece, and the second isolation film in sequence and then winding them, or it can be formed by stacking the first isolation film, the first pole piece, the second isolation film, and the second pole piece in sequence and then winding them.
[0010] It can be understood that the first isolation membrane and the second isolation membrane each have two sides, and the first isolation membrane and the second isolation membrane can represent two sections of different parts of an isolation membrane, or can represent two isolation membranes respectively. In the lithium-ion battery of the present application, one side of the first isolation membrane and the second isolation membrane can face the center of the electrode assembly, and the other side can face away from the center of the electrode assembly. The inventors have found that by setting a first adhesive layer on the surface of the first isolation membrane and / or the second isolation membrane away from the center of the electrode assembly, the first isolation membrane and / or the second isolation membrane extend from the tail end of the electrode assembly, so that the first isolation membrane and / or the second isolation membrane are bonded to the shell through the first adhesive layer, the electrode assembly and the shell can be made into a whole, the safety of the lithium-ion battery is improved, and the influence of the additional double-sided adhesive between the electrode assembly and the shell on the energy density of the lithium-ion battery can be effectively avoided.
[0011] In a first possible implementation, a first adhesive layer is disposed on a surface of the first isolation film away from the center of the electrode assembly, the first isolation film extends from the tail end of the electrode assembly, and the first isolation film is bonded to the shell through the first adhesive layer;
[0012] In a second possible implementation, a first adhesive layer is disposed on a surface of the second isolation film away from the center of the electrode assembly, the second isolation film extends from the tail end of the electrode assembly, and the second isolation film is bonded to the shell through the first adhesive layer;
[0013] In a third possible implementation, the first isolation film and the second isolation film are both provided with a first adhesive layer on the surface facing away from the center of the electrode assembly, the first isolation film and the second isolation film extend from the tail end of the electrode assembly, and the first isolation film and the second isolation film are bonded to the shell through the first adhesive layer. The present application does not particularly limit the bonding method of the first isolation film and the second isolation film to the shell. For example, the second isolation film can be first bonded to the first isolation film through the first adhesive layer on its surface, and then the first isolation film is bonded to the shell through the first adhesive layer on its surface; or, the portion of the second isolation film that extends out can slightly exceed the portion of the first isolation film that extends out, the second isolation film can first be bonded to the first isolation film through the first adhesive layer on its surface, and the first adhesive layer of the portion that exceeds the first isolation film is then bonded to the shell, and the first isolation film is then bonded to the shell through the first adhesive layer on its surface.
[0014] The inventors also found that the bonding area between the first adhesive layer and the shell should not be too small, otherwise it may affect the bonding performance between the first adhesive layer and the shell. By making the bonding area between the first adhesive layer and the shell greater than or equal to 10% of the contact area between the shell and the electrode assembly, the electrode assembly and the shell can be tightly bonded together. The bonding area between the first adhesive layer and the shell mentioned in this application may refer to the area of the bonding area after the first adhesive layer and the shell are bonded. The tail end mentioned in this application may refer to the tail end of the outermost electrode sheet in a lithium-ion battery (or electrode assembly) with a wound structure.
[0015] The present application has no particular restrictions on the shell, for example, it can be a packaging bag or other structure that can package the electrode assembly. The electrode assembly referred to in the present application can be a lithium-ion battery that has not been packaged and has not been injected with electrolyte. The first pole piece and the second pole piece in the present application have opposite polarities. In an optional embodiment, the first pole piece is a positive pole piece, the second pole piece is a negative pole piece, and the second pole piece may also include a second current collector.
[0016] In one embodiment of the present application, a second adhesive layer is further provided on the surface of the first isolation film and / or the second isolation film facing the center of the electrode assembly, and the first isolation film and / or the second isolation film extend from the tail end of the second pole piece and are bonded to the first current collector through the second adhesive layer. The above arrangement makes the electrode assembly more firmly bonded to the shell, further improving the safety of the lithium-ion battery.
[0017] Among them, in a first possible implementation manner, a second adhesive layer is further provided on the surface of the first isolation film facing the center of the electrode assembly, and the first isolation film extends from the tail end of the second electrode sheet and is bonded to the first current collector through the second adhesive layer, so that the side of the first isolation film away from the center of the electrode assembly is bonded to the shell through the first adhesive layer, and the side of the first isolation film facing the center of the electrode assembly is bonded to the first current collector through the second adhesive layer;
[0018] In a second possible implementation, a second adhesive layer is further provided on the surface of the second isolation film facing the center of the electrode assembly, and the second isolation film extends from the tail end of the second electrode sheet and is bonded to the first current collector through the second adhesive layer, so that the side of the second isolation film facing away from the center of the electrode assembly is bonded to the shell through the first adhesive layer, and the side of the second isolation film facing the center of the electrode assembly is bonded to the first current collector through the second adhesive layer;
[0019] In a third possible implementation, the surfaces of the first isolation film and the second isolation film facing the center of the electrode assembly are both provided with a second adhesive layer, and the first isolation film and the second isolation film both extend from the tail end of the second electrode sheet. The present application does not particularly limit the bonding method of the first isolation film and the second isolation film to the shell. For example, the first isolation film can be first bonded to the shell through the first adhesive layer on the side facing away from the center of the electrode assembly, and then bonded to the side of the second isolation film facing away from the center of the electrode assembly through the second adhesive layer on the side facing the center of the electrode assembly, and then the side of the second isolation film facing the center of the electrode assembly is bonded to the first current collector through the second adhesive layer on its surface.
[0020] In one embodiment of the present application, the surface of the first isolation membrane facing away from the center of the electrode assembly faces the surface of the first pole piece facing the center of the electrode assembly, and the surface of the first isolation membrane facing the center of the electrode assembly faces the surface of the second pole piece facing away from the center of the electrode assembly.
[0021] In one embodiment of the present application, the surface of the second isolation membrane away from the center of the electrode assembly faces the surface of the second pole piece toward the center of the electrode assembly, and the surface of the second isolation membrane toward the center of the electrode assembly faces the surface of the first pole piece away from the center of the electrode assembly.
[0022] In one embodiment of the present application, in the region where the first isolation film or the second isolation film is bonded to the shell, the bonding force F1 between the first isolation film or the second isolation film and the shell is 5N / m to 55N / m. In a first possible embodiment, when the first isolation film is bonded to the shell, in the region where the first isolation film is bonded to the shell, the bonding force F1 between the first isolation film and the shell is 5N / m to 55N / m; in a second possible embodiment, when the second isolation film is bonded to the shell, in the region where the second isolation film is bonded to the shell, the bonding force F1 between the second isolation film and the shell is 5N / m to 55N / m. By controlling the bonding force F1 within the above range, the bonding performance between the isolation film and the shell can be further improved.
[0023] In one embodiment of the present application, the adhesion force F2 between the first isolation film or the second isolation film and the first current collector is 5.01 N / m to 60 N / m. By controlling the adhesion force F2 within the above range, the bonding performance between the isolation film and the housing can be further improved.
[0024] Among them, in a first possible implementation manner, when the first isolation film is bonded to the first current collector, the bonding force F2 between the first isolation film and the first current collector is 5.01 N / m to 60 N / m; in a second possible implementation manner, when the second isolation film is bonded to the first current collector, the bonding force F2 between the second isolation film and the first current collector is 5.01 N / m to 60 N / m.
[0025] In one embodiment of the present application, the adhesion between the first isolation film and the surface of the first current collector facing away from the center of the electrode assembly is F2, and the adhesion between the first isolation film and the shell is F1, then the difference between F2 and F1 is 1N / m to 15N / m. Alternatively, the adhesion between the second isolation film and the surface of the first current collector facing away from the center of the electrode assembly is F2, and the adhesion between the second isolation film and the shell is F1, then the difference between F2 and F1 is 1N / m to 15N / m. The above-mentioned setting makes the two sides of the isolation film evenly stressed, avoiding damage caused by uneven stress on both sides during the fall of the lithium-ion battery, thereby further improving the safety of the lithium-ion battery.
[0026] In one embodiment of the present application, along the winding direction of the electrode assembly, the bonding area between the portion of the first isolation membrane that exceeds the tail end of the second pole piece and the surface of the first current collector that faces away from the center of the electrode assembly is S1, and the bonding area between the portion of the first isolation membrane that exceeds the tail end of the second pole piece and the shell is S2, then S1 is greater than S2. Alternatively, the bonding area between the portion of the second isolation membrane that exceeds the tail end of the second pole piece and the surface of the first current collector that faces away from the center of the electrode assembly is S1, and the bonding area between the portion of the second isolation membrane that exceeds the tail end of the second pole piece and the shell is S2, then S1 is greater than S2. The above-mentioned arrangement makes the bonding force between the isolation membrane and the surface of the first current collector that faces away from the center of the electrode assembly stronger and the bonding is more reliable, thereby ensuring that the electrode assembly is bonded as a whole, effectively preventing the structure of the lithium-ion battery from being damaged during a fall, and further improving the safety of the lithium-ion battery.
[0027] In one embodiment of the present application, along the winding direction of the electrode assembly, the first separator extends from the end of the electrode assembly, and the second separator extends beyond the end of the second pole piece and does not extend beyond the end of the first pole piece. In the above arrangement, the first separator can wrap the second separator, so that the first separator has more area to bond with the first current collector, and can improve the current collector (aluminum foil) tearing or the second separator eversion problem, further improving the safety of the lithium-ion battery.
[0028] In one embodiment of the present application, the first adhesive layer and the second adhesive layer include high molecular polymers, so that the first adhesive layer and the second adhesive layer have excellent bonding properties.
[0029] In one embodiment of the present application, the monomers forming the high molecular weight polymer may include two monomers, wherein the first monomer is propylene, and the second monomer includes at least one of ethylene, vinylidene fluoride, vinyl chloride, butadiene, isoprene, styrene, acrylonitrile, ethylene oxide, propylene oxide, acrylate, vinyl acetate or caprolactone. When selecting a combination of multiple monomers to provide the second monomer, the ratio between the monomers is not specifically limited and can be any ratio as long as the requirements of the present application are met.
[0030] In one embodiment of the present application, the high molecular polymer is a particle, and the average particle size of the particle is 1 μm to 10 μm, preferably 2 μm to 5 μm. The particle size of the high molecular polymer of the present application is within the above range, which can better play a bonding role in the adhesive layer.
[0031] In one embodiment of the present application, the thickness of the first glue layer and the second glue layer is 1 μm to 50 μm, preferably 2 μm to 30 μm, and more preferably 3 μm to 15 μm. When the thickness of the glue layer is too small (for example, less than 1 μm), the bonding force between the glue layer and the shell is small. When the thickness of the glue layer is too large (for example, greater than 50 μm), the relative content of active materials in the lithium-ion battery decreases, affecting the energy density of the lithium-ion battery. Without being limited to any theory, controlling the thickness of the glue layer within the above range can further improve the bonding performance between the isolation membrane and the shell, while having little effect on the energy density of the lithium-ion battery.
[0032] In one embodiment of the present application, the first monomer accounts for 30 mol% to 95 mol% of the total monomers forming the high molecular polymer, preferably 50 mol% to 90 mol%, more preferably 60 mol% to 80 mol%, and the second monomer accounts for 5 mol% to 70 mol% of the total monomers forming the high molecular polymer, preferably 10 mol% to 50 mol%, more preferably 20 mol% to 40 mol%. By controlling the contents of the first monomer and the second monomer within the above range, a high molecular polymer with excellent bonding properties can be obtained.
[0033] In one embodiment of the present application, the isotacticity of the high molecular polymer is 45% to 80%, preferably 60% to 80%. When the isotacticity of the high molecular polymer is within the above range, a glue layer with appropriate softening temperature and good adhesion can be obtained.
[0034] In one embodiment of the present application, the softening temperature of the polymer is 130°C to 170°C, preferably 155°C to 170°C. By controlling the softening temperature of the polymer of the present application, the polymer of the present application can have better bonding properties. In particular, when the adhesive layer of the present application contains the above-mentioned polymer, the bonding performance between the isolation film extending from the tail end of the electrode assembly and the shell can be improved, further improving the safety of the lithium-ion battery.
[0035] In one embodiment of the present application, the weight average molecular weight of the high molecular weight polymer is 5000 g / mol to 1000000 g / mol, preferably 10000 g / mol to 500000 g / mol. When the weight average molecular weight is within the above range, a high molecular weight polymer with good adhesion can be obtained.
[0036] The inventors found that when a lithium-ion battery falls, the shell is impacted first, and the internal electrode assembly and the shell are relatively displaced, and the thinner electrode pole piece is more easily torn than the thicker shell. In one embodiment of the present application, the bonding force between the first isolation film and the first pole piece is greater than the bonding force between the first isolation film and the shell, thereby ensuring that the electrode assembly is bonded as a whole, effectively preventing the structure of the lithium-ion battery from being damaged during the fall, and further improving the safety of the lithium-ion battery.
[0037] There is no particular limitation on the preparation method of the high molecular weight polymer of the present application, and a preparation method known to those skilled in the art can be used, which can be selected according to the type of monomers used, such as a solution method, a slurry method, a gas phase method, and the like.
[0038] For example, when the second monomer is selected from ethylene, the following method can be used:
[0039] The main catalyst and the co-catalyst are respectively dissolved in hexane to obtain a hexane solution of the main catalyst and a hexane solution of the co-catalyst, and then the hexane is added into the reactor. Then, the hexane solution of the main catalyst and the hexane solution of the co-catalyst are added into the reactor under the protection of nitrogen, and then propylene and ethylene are introduced. The temperature is raised to 50°C to 60°C. During the reaction, the pressure in the reactor is maintained at 0.3MPa to 0.5MPa. After reacting for 0.5h to 2h, the reaction is terminated with acidified ethanol. The product is washed with anhydrous ethanol for 3 to 5 times, filtered, and dried in a vacuum drying oven at 50°C to 70°C for 3h to 5h.
[0040] The present application has no particular restrictions on the main catalyst and the co-catalyst, as long as the purpose of the present invention can be achieved. For example, a metallocene catalytic system is used, wherein the main catalyst includes a metallocene complex (such as ferrocene or its derivatives), and the co-catalyst includes methylaluminoxane; and the present application has no particular restrictions on the amount of the main catalyst and the co-catalyst added, as long as the purpose of the present invention can be achieved. In addition, the reactor can be vacuum evacuated before the reaction, and then the reactor can be replaced with nitrogen 3 to 5 times to make the reactor clean.
[0041] When the second monomer is selected from butadiene, the preparation method of the propylene-ethylene copolymer is the same as the preparation method of the propylene-ethylene copolymer except that the ethylene in the preparation method of the propylene-ethylene copolymer is replaced by butadiene.
[0042] When the second monomer is selected from acrylic ester, the difference from the above-mentioned method for preparing propylene-ethylene copolymer is that the ethylene in the method for preparing propylene-ethylene copolymer is replaced by acrylic ester, and under the protection of nitrogen, hexane, a hexane solution of the main catalyst, and a hexane solution of the co-catalyst are added to the reactor, and then acrylic ester is added, and then propylene is introduced, and the rest is the same as the above-mentioned method for preparing propylene-ethylene copolymer.
[0043] The acrylate monomer may be selected from any one of methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, isooctyl acrylate or hydroxyethyl acrylate.
[0044] The copolymerization of other monomers is not listed one by one in this application, and the preparation methods known in the art can be adopted.
[0045] There is no particular restriction on the positive electrode sheet in the present application, as long as the purpose of the present application can be achieved. For example, the positive electrode sheet generally comprises a positive current collector and a positive active material layer. Among them, the positive current collector is not particularly limited, and can be any positive current collector known in the art, such as aluminum foil, aluminum alloy foil or composite current collector. The positive active material layer includes a positive active material, and the positive active material is not particularly limited. Any positive active material known in the art can be used, for example, it can include lithium nickel cobalt manganese oxide (811, 622, 523, 111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide, lithium manganese oxide, lithium iron manganese phosphate or lithium titanate. At least one of.
[0046] There is no particular limitation on the negative electrode plate in the present application, as long as the purpose of the present application can be achieved. For example, the negative electrode plate generally comprises a negative electrode current collector and a negative electrode active material layer. Among them, the negative electrode current collector is not particularly limited, and any negative electrode current collector known in the art can be used, such as copper foil, aluminum foil, aluminum alloy foil, and composite current collector. The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material is not particularly limited, and any negative electrode active material known in the art can be used. For example, it can include at least one of artificial graphite, natural graphite, mesophase carbon microbeads, soft carbon, hard carbon, silicon, silicon carbon, lithium titanate, etc.
[0047] The lithium-ion battery of the present application further comprises an electrolyte, which may be one or more of a gel electrolyte, a solid electrolyte and an electrolyte, wherein the electrolyte comprises a lithium salt and a non-aqueous solvent.
[0048] In some embodiments of the present application, the lithium salt is selected from one or more of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB and lithium difluoroborate. For example, the lithium salt can be selected from LiPF6 because it can provide high ionic conductivity and improve cycle characteristics. The non-aqueous solvent can be a carbonate compound, a carboxylate compound, an ether compound, other organic solvents or a combination thereof. The above-mentioned carbonate compound can be a linear carbonate compound, a cyclic carbonate compound, a fluorinated carbonate compound or a combination thereof.
[0049] Examples of the above-mentioned linear carbonate compounds are dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC) and combinations thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC) and combinations thereof. Examples of fluorocarbonate compounds are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate and combinations thereof.
[0050] Examples of the above carboxylic acid ester compounds are methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanoic acid lactone, valerolactone, mevalonolactone, caprolactone and combinations thereof.
[0051] Examples of the above ether compound are dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, and combinations thereof.
[0052] Examples of the above other organic solvents are dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphoric acid esters and combinations thereof.
[0053] The present application also provides an electronic device, which includes the electrochemical device described in any of the above embodiments of the present application and has good safety performance.
[0054] The electronic device of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0055] The preparation process of the electrochemical device is well known to those skilled in the art and is not particularly limited in this application. For example, a lithium-ion battery can be manufactured by overlapping the positive electrode and the negative electrode via a separator, winding them as needed and placing them in a shell, allowing the separator to extend from the end of the electrode assembly and bonded to the shell through a first adhesive layer, injecting the electrolyte into the shell and sealing it. In addition, an overcurrent protection element, a guide plate, etc. can also be placed in the shell as needed to prevent the pressure inside the lithium-ion battery from rising and overcharging and discharging.
[0056] In the present application, the term "isotacticity" refers to the percentage of isotactic polymer in the total amount of high molecular weight polymer.
[0057] The term "particle size" refers to the average particle size of the polymer particles.
[0058] The present application provides an electrochemical device and an electronic device, which includes a shell and a wound electrode assembly disposed in the shell, wherein a first adhesive layer is disposed on the surface of the first isolation film and / or the second isolation film away from the center of the electrode assembly, the first isolation film and / or the second isolation film extend from the end of the electrode assembly and are bonded to the shell through the first adhesive layer, and the area of the first adhesive layer bonded to the shell is greater than or equal to 10% of the contact area between the shell and the electrode assembly, so that the electrode assembly and the shell are tightly bonded together, thereby improving the safety of the lithium-ion battery. In addition, since it is no longer necessary to additionally set double-sided adhesive between the electrode assembly and the shell, the influence of the additional double-sided adhesive on the energy density of the lithium-ion battery can be avoided. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] In order to more clearly illustrate the technical solutions of the present application and the prior art, the following briefly introduces the drawings required for use in the embodiments and the prior art. Obviously, the drawings described below are only some embodiments of the present application.
[0060] Figure 1 A schematic diagram of the structure of an electrochemical device in one embodiment of the present application;
[0061] Figure 2 A schematic diagram of the structure of an electrochemical device in another embodiment of the present application;
[0062] Figure 3 A schematic diagram of the structure of an electrochemical device in another embodiment of the present application;
[0063] Figure 4 is a schematic structural diagram of an electrochemical device in a fourth embodiment of the present application;
[0064] Figure 5 is a schematic structural diagram of an electrochemical device in a fifth embodiment of the present application;
[0065] Figure 6 is a schematic structural diagram of an electrochemical device in a sixth embodiment of the present application;
[0066] Figure 7 is a schematic structural diagram of an electrochemical device in a seventh embodiment of the present application;
[0067] Figure 8 is a schematic structural diagram of an electrochemical device in an eighth embodiment of the present application;
[0068] Figure 9a A schematic diagram of a bonding method between the first adhesive layer of the isolation film and the housing in one embodiment of the present application;
[0069] Figure 9b This is a schematic diagram of a bonding method between the first adhesive layer of the isolation film and the housing in another embodiment of the present application;
[0070] Fig.9c This is a schematic diagram of a bonding method between the first adhesive layer of the isolation film and the housing in another embodiment of the present application;
[0071] Fig.10 This is a schematic diagram of the structure of the lithium-ion battery in Example 1 of the present application;
[0072] Fig.11 This is a schematic diagram of the structure of the lithium-ion battery in Example 2 of the present application;
[0073] Fig.12 This is a schematic diagram of the structure of the lithium-ion battery in Example 3 of the present application;
[0074] Fig.13 This is a schematic diagram of the structure of the lithium-ion battery in Example 4 of the present application;
[0075] Fig.14 This is a schematic diagram of the structure of the lithium-ion battery in Example 5 of the present application;
[0076] Fig.15 Schematic diagram of the structure of the lithium ion battery of Comparative Example 1.
[0077] In the figure, 1. first pole piece, 2. second pole piece, 4. shell, 6. pole ear, 7. first adhesive layer, 8. second adhesive layer, 11. first current collector, 21. second current collector, 31. first isolation membrane, 32. second isolation membrane. DETAILED DESCRIPTION
[0078] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail with reference to the accompanying drawings and embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0079] It should be noted that in the specific embodiments of the present application, a lithium-ion battery is used as an example of an electrochemical device to explain the present application, but the electrochemical device of the present application is not limited to a lithium-ion battery.
[0080] Figure 1 A schematic diagram of the structure of an electrochemical device in one embodiment of the present application is shown in FIG. Figure 1 As shown, it includes a housing 4 and a wound electrode assembly disposed in the housing 4, the electrode assembly includes a first pole piece 1, a second pole piece 2 having a polarity opposite to that of the first pole piece 1, a first isolation film 31 or a second isolation film 32 is disposed between the first pole piece 1 and the second pole piece 2, and the first pole piece 1 includes a first current collector 11. Among them, a first adhesive layer 7 is disposed on the surface of the first isolation film 31 away from the center O of the electrode assembly, the first isolation film 31 extends from the tail end of the electrode assembly, and the first isolation film 31 is bonded to the housing 4 through the first adhesive layer 7. Figure 1 The pole ear 6 is also shown in the figure. The second pole piece 2 may also include a second current collector 21.
[0081] Figure 2 is a schematic diagram of the structure of an electrochemical device in another embodiment of the present application, such as Figure 2 As shown, a first adhesive layer 7 is provided on the surface of the second isolation film 32 away from the center of the electrode assembly. The second isolation film 32 extends from the tail end of the electrode assembly. The second isolation film 32 is bonded to the shell 4 through the first adhesive layer 7 .
[0082] Figure 3 This is a schematic diagram of the structure of an electrochemical device in another embodiment of the present application, such as Figure 3 As shown, the first isolation film 31 and the second isolation film 32 are both provided with a first adhesive layer 7 on their surfaces facing away from the center of the electrode assembly. The first isolation film 31 and the second isolation film 32 extend from the tail end of the electrode assembly, and the first isolation film 31 and the second isolation film 32 are bonded to the shell 4 through the first adhesive layer 7.
[0083] Figure 4 Schematic diagram of the structure of the electrochemical device in the fourth embodiment of the present application, such as Figure 4 As shown, the surface of the first isolation film 31 facing the center of the electrode assembly is also provided with a second adhesive layer 8. The first isolation film 31 extends from the tail end of the second pole piece 2 and is bonded to the first current collector 11 through the second adhesive layer 8, so that the side of the first isolation film 31 facing away from the center of the electrode assembly is bonded to the shell 4 through the first adhesive layer 7, and the side of the first isolation film 31 facing the center of the electrode assembly is bonded to the first current collector 11 through the second adhesive layer 8.
[0084] Figure 5 This is a schematic diagram of the structure of the electrochemical device in the fifth embodiment of the present application, such as Figure 5As shown, a second adhesive layer 8 is also provided on the surface of the second isolation film 32 facing the center of the electrode assembly. The second isolation film 32 extends from the tail end of the second pole piece 2 and is bonded to the first current collector 11 through the second adhesive layer 8, so that the side of the second isolation film 32 facing away from the center of the electrode assembly is bonded to the shell 4 through the first adhesive layer 7, and the side of the second isolation film 32 facing the center of the electrode assembly is bonded to the first current collector 11 through the second adhesive layer 8.
[0085] Figure 6 Schematic diagram of the structure of the electrochemical device in the sixth embodiment of the present application, such as Figure 6 As shown, the surfaces of the first isolation film 31 and the second isolation film 32 facing the center of the electrode assembly are both provided with a second adhesive layer 8, and the first isolation film 31 and the second isolation film 32 both extend from the tail end of the second pole piece 2. The first isolation film 31 can be firstly bonded to the housing 4 through the first adhesive layer 7 on the side away from the center of the electrode assembly, and then bonded to the side of the second isolation film 32 away from the center of the electrode assembly through the second adhesive layer 8 on the side facing the center of the electrode assembly, and then, the side of the second isolation film 32 facing the center of the electrode assembly is bonded to the first current collector 11 through the second adhesive layer 8 on its surface.
[0086] Figure 7 Schematic diagram of the structure of the electrochemical device in the sixth embodiment of the present application, such as Figure 7 As shown, along the winding direction of the electrode assembly, the bonding area between the portion of the first isolation film 31 extending beyond the tail end of the second pole piece 2 and the first current collector 11 is larger than the bonding area between the portion of the first isolation film 31 extending beyond the tail end of the second pole piece 2 and the shell 4.
[0087] Figure 8 Schematic diagram of the structure of a lithium-ion battery in the eighth embodiment of the present application, such as Figure 8 As shown, in the lithium-ion battery, the first isolation membrane 31 extends from the tail end of the electrode assembly, the second isolation membrane 32 extends beyond the tail end of the second pole piece 2 and does not extend beyond the tail end of the first pole piece 1, and the first isolation membrane 31 wraps the second isolation membrane 32, so that the first isolation membrane 31 has more area to bond with the first current collector 11, and can improve the problem of current collector (aluminum foil) tearing or second isolation membrane 32 everting.
[0088] Figure 9a Schematic diagram of the bonding method between the first adhesive layer of the isolation film and the housing in one embodiment of the present application. The width w1 of the first adhesive layer can be equal to the width w2 of the housing, or slightly smaller than the width w2 of the housing. Figure 9b Schematic diagram of the bonding method between the first adhesive layer of the isolation film and the housing in another embodiment of the present application. The width w1 of the first adhesive layer may be smaller than the width w2 of the housing. Fig.9cThis is a schematic diagram of the bonding method between the first adhesive layer of the isolation film and the shell in another embodiment of the present application. The width w1 of the first adhesive layer can be smaller than the width w2 of the shell, and the end of the first adhesive layer can be an irregular shape (for example, a wavy shape). Figures 9a to 9c In the bonding method of the adhesive layer of the isolation film and the shell shown, it is sufficient as long as the bonding area of the first adhesive layer and the shell is greater than or equal to 10% of the contact area between the shell and the electrode assembly.
[0089] Example
[0090] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0091] Test methods and equipment:
[0092] Lithium-ion battery drop test:
[0093] After the lithium-ion battery is fully charged according to the 0.5C charging system, it is left open for 2 hours to measure the thickness, voltage and internal resistance of the lithium-ion battery; the lithium-ion battery to be tested is dropped freely from a height of 1.2m onto a horizontal hardwood board with a thickness of 18mm to 20mm. All six sides of the lithium-ion battery must be dropped, and the total number of drops for each lithium-ion battery is 6 times. The lithium-ion battery is required to have no obvious deformation, no leakage, no fire, and no explosion, otherwise it will fail the test.
[0094] Heavy object impact test:
[0095] After the lithium-ion battery is fully charged according to the 0.5C charging system, it is placed in an open circuit for 2 hours. According to the provisions of Article 7.7 of the national standard GB31241-2014, a 15.8mm±0.2mm metal bar is placed horizontally on the upper surface of the geometric center of the lithium-ion battery, and a weight of 9.1kg±0.1kg is used to hit the surface of the lithium-ion battery with the metal bar in a free fall state from a height of 610mm±25mm, and observed for 6 hours. The battery is required to not leak, catch fire, or explode, otherwise the test fails.
[0096] Adhesion test:
[0097] The finished lithium-ion battery after discharge was disassembled, and the part where the separator (the first separator or the second separator) was bonded to the first pole piece and the part where the separator was bonded to the shell were cut into strip samples of 10 mm × 100 mm, respectively. The samples were adhered to a stainless steel plate with double-sided tape, and the adhesion between the separator and the first pole piece and the shell was tested by a 180° peel force test method, with a test speed of 300 mm / min and a test length of 40 mm.
[0098] Test of polymer weight average molecular weight:
[0099] The weight average molecular weight of the polymer is tested by gel permeation chromatography (GPC). In the present application, the weight average molecular weight refers to the molecular weight averaged by mass.
[0100] Polymer softening temperature test:
[0101] A universal differential scanning calorimeter (DSC) method was used: 5 mg of a polymer sample was weighed, the temperature was raised to 150° C. at a heating rate of 5° C. / min, a DSC curve was collected, and the softening temperature of the polymer was determined from the obtained DSC curve.
[0102] Polymer isotacticity test:
[0103] The isotacticity of the polymer is tested according to the FTIR (Fourier Transform Infrared Spectroscopy) method, wherein the FTIR method adopts the national standard GB / T 21186-2007 "Fourier Transform Infrared Spectrometer".
[0104] Example 1
[0105] <1-1. Preparation of First Separator Film>
[0106] <1-1-1. Preparation of high molecular weight polymer>
[0107] In a 1L stainless steel reactor, 77 parts (volume fraction) of hexane solvent, 19 parts (volume fraction) of the main catalyst ferrocene hexane solution (ferrocene content 70mg / L), 4 parts (volume fraction) of the co-catalyst methylaluminoxane hexane solution (methylaluminoxane content 10mg / L) were added under nitrogen protection, and then vinylidene fluoride (PVDF) was added, and then propylene was introduced, and the temperature was raised to 50°C, and the pressure of the reactor was controlled to 0.4MPa. The molar ratio between the first and second monomers was adjusted to 60:40 by adjusting the amount of propylene / vinylidene fluoride added. After reacting for 1h, the reaction was terminated with acidified ethanol to obtain propylene-vinylidene fluoride copolymer. The obtained product was washed with anhydrous ethanol for 3 times, filtered, and dried in a vacuum drying oven at 60°C for 4h. The average particle size of the obtained high molecular polymer was 2μm, the softening temperature was 170°C, the isotacticity was 80%, and the weight average molecular weight was 100000g / mol.
[0108] <1-1-2. Preparation of glue layer slurry>
[0109] Polyvinylidene fluoride (PVDF), polyacrylic acid (PAA) and the prepared high molecular polymer are mixed in a mass ratio of 70:10:20 to obtain a mixture, and then the mixture is dissolved in acetone to obtain a glue layer slurry with a solid content of 40%.
[0110] <1-1-3. Preparation of Separator Film Containing Substrate Layer>
[0111] The adhesive layer slurry was evenly coated on the two surfaces of the end of the polyethylene (PE) isolation film substrate with a thickness of 9 μm to form a first adhesive layer and a second adhesive layer, the thickness of the first adhesive layer and the second adhesive layer were 3 μm respectively. The second isolation film was prepared in the same way.
[0112] <1-2. Preparation of positive electrode sheet>
[0113] The positive electrode active materials lithium cobalt oxide, acetylene black, and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 94:3:3, and then N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 75%, and stirred evenly. The slurry is evenly coated on one surface of an aluminum foil with a thickness of 12 μm, dried at 90°C, and cold pressed to obtain a positive electrode sheet with a positive electrode active material layer thickness of 100 μm, and then the above steps are repeated on the other surface of the positive electrode sheet to obtain a positive electrode sheet coated with a positive electrode active material layer on both sides. The positive electrode sheet is welded to the pole ear and set aside.
[0114] <1-3. Preparation of negative electrode sheet>
[0115] Mix the negative electrode active materials artificial graphite, acetylene black, styrene-butadiene rubber and sodium carboxymethyl cellulose in a mass ratio of 96:1:1.5:1.5, then add deionized water as a solvent, prepare a slurry with a solid content of 70%, and stir evenly. The slurry is evenly coated on one surface of a copper foil with a thickness of 8 μm, dried at 110°C, and cold pressed to obtain a negative electrode sheet with a negative electrode active material layer coated on one side with a thickness of 150 μm, and then repeat the above coating steps on the other surface of the negative electrode sheet to obtain a negative electrode sheet with a negative electrode active material layer coated on both sides. Weld the negative electrode sheet to the pole ear and set aside.
[0116] <1-4. Preparation of electrolyte>
[0117] In an environment with a water content of less than 10ppm, non-aqueous organic solvents of ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), propyl propionate (PP), and vinylene carbonate (VC) are mixed in a mass ratio of 20:30:20:28:2, and then lithium hexafluorophosphate (LiPF6) is added to the non-aqueous organic solvent to dissolve and mix evenly to obtain an electrolyte, wherein the mass ratio of LiPF6 to the non-aqueous organic solvent is 8:92.
[0118] <1-5. Preparation of lithium-ion batteries>
[0119] The positive electrode sheet, the first separator, the negative electrode sheet, and the second separator prepared above are stacked in order, so that the first separator and the second separator are located between the positive electrode sheet and the negative electrode sheet to play a role of isolation, and are wound to obtain an electrode assembly, and the electrode assembly is placed in a shell (aluminum-plastic film packaging bag), so that the first separator extends from the end of the electrode assembly and the first adhesive layer at the end of the first separator is bonded to the shell (aluminum-plastic film packaging bag) by hot pressing, and the bonding area of the first adhesive layer to the shell is 10% of the contact area between the shell and the electrode assembly (such as Fig.10 The electrolyte is prepared by removing moisture at 80°C, and a lithium-ion battery is obtained through vacuum packaging, standing, forming, and shaping processes.
[0120] Example 2
[0121] Except in the preparation of lithium-ion batteries, the area where the first adhesive layer is bonded to the shell is 20% of the contact area between the shell and the electrode assembly (such as Fig.11 Except for the region a shown in the figure, the rest is the same as in Example 1.
[0122] Example 3
[0123] Except in the preparation of lithium-ion batteries, the area where the first adhesive layer is bonded to the shell is 30% of the contact area between the shell and the electrode assembly (such as Fig.12 Except for the region a shown in the figure, the rest is the same as in Example 1.
[0124] Example 4
[0125] Except in the preparation of lithium-ion batteries, the area where the first adhesive layer is bonded to the shell is 50% of the contact area between the shell and the electrode assembly (such as Fig.13 Except for the region a shown in the figure, the rest is the same as in Example 1.
[0126] Example 5
[0127] Except in the preparation of lithium-ion batteries, the area where the first adhesive layer is bonded to the shell is 100% of the contact area between the shell and the electrode assembly (such as Fig.14 Except for the region a shown in the figure, the rest is the same as in Example 1.
[0128] Example 6
[0129] The process is the same as that of Example 3 except that in the preparation of adhesive layer, polyvinylidene fluoride (PVDF), polyacrylic acid (PAA) and the prepared high molecular polymer are mixed in a mass ratio of 60:10:30.
[0130] Example 7
[0131] The process is the same as that of Example 3 except that in <Preparation of Adhesive Layer>, polyvinylidene fluoride (PVDF), polyacrylic acid (PAA) and the prepared high molecular polymer are mixed in a mass ratio of 50:10:40.
[0132] Example 8
[0133] The process is the same as that of Example 3 except that in <Preparation of Adhesive Layer>, polyvinylidene fluoride (PVDF), polyacrylic acid (PAA) and the prepared high molecular polymer are mixed in a mass ratio of 40:10:50.
[0134] Example 9
[0135] The process is the same as Example 7 except that the softening temperature of the polymer is adjusted to 160° C. and the isotacticity is adjusted to 70% in the preparation of polymer.
[0136] Example 10
[0137] The process is the same as Example 7 except that the softening temperature of the polymer is adjusted to 155° C. and the isotacticity is adjusted to 65% in the preparation of polymer.
[0138] Embodiment 11
[0139] The process is the same as Example 7 except that the softening temperature of the polymer is adjusted to 150° C. and the isotacticity is adjusted to 60% in the preparation of the polymer.
[0140] Example 12
[0141] The process is the same as Example 7 except that the softening temperature of the polymer is adjusted to 140° C. and the isotacticity is adjusted to 55% in the preparation of polymer.
[0142] Example 13
[0143] The process is the same as Example 7 except that the softening temperature of the polymer is adjusted to 135° C. and the isotacticity is adjusted to 50% in the preparation of the polymer.
[0144] Embodiment 14
[0145] The process is the same as Example 7 except that the softening temperature of the polymer is adjusted to 130° C. and the isotacticity is adjusted to 45% in “Preparation of polymer”.
[0146] Embodiment 15
[0147] Except for the difference in <Preparation of High Molecular Polymer> from Example 5, the rest is the same as Example 5.
[0148] <Preparation of high molecular weight polymer>
[0149] In a 1L stainless steel reactor, 77 parts (volume fraction) of hexane solvent, 19 parts (volume fraction) of a hexane solution of a main catalyst ferrocene (ferrocene content 70 mg / L), and 4 parts (volume fraction) of a hexane solution of a co-catalyst methylaluminoxane (methylaluminoxane content 10 mg / L) were added under nitrogen protection, and then a propylene / butadiene mixed gas was introduced, the temperature was raised to 50°C, and the pressure of the reactor was controlled at 0.4MPa. The amount of propylene / butadiene added was adjusted so that the molar ratio between the first and second monomers was 30:70. After reacting for 1 hour, the reaction was terminated with acidified ethanol to obtain a propylene-butadiene copolymer. The obtained product was washed 3 times with anhydrous ethanol, filtered, and dried in a vacuum drying oven at 60°C for 4 hours.
[0150] Example 16
[0151] Except for the difference in <Preparation of High Molecular Polymer> from Example 5, the rest is the same as Example 5.
[0152] <Preparation of high molecular weight polymer>
[0153] In a 1L stainless steel reactor, 77 parts (volume fraction) of hexane solvent, 19 parts (volume fraction) of a hexane solution of the main catalyst ferrocene (ferrocene content 70 mg / L), and 4 parts (volume fraction) of a hexane solution of the co-catalyst methylaluminoxane (methylaluminoxane content 10 mg / L) were added under nitrogen protection, and then ethyl acrylate was added, and then propylene was introduced. The temperature was raised to 50°C, and the pressure of the reactor was controlled to be 0.4MPa. The molar ratio between the first and second monomers was adjusted to 30:70 by adjusting the amount of propylene / ethyl acrylate added. After reacting for 1 hour, the reaction was terminated with acidified ethanol to obtain a propylene-ethyl acrylate copolymer. The resulting product was washed 3 times with anhydrous ethanol, filtered, and dried in a vacuum drying oven at 60°C for 4 hours.
[0154] Embodiment 17
[0155] Except for the difference in <Preparation of High Molecular Polymer> from Example 5, the rest is the same as Example 5.
[0156] <Preparation of high molecular weight polymer>
[0157] In a 1L stainless steel reactor, 77 parts (volume fraction) of hexane solvent, 19 parts (volume fraction) of a hexane solution of a main catalyst ferrocene (ferrocene content 70 mg / L), and 4 parts (volume fraction) of a hexane solution of a co-catalyst methylaluminoxane (methylaluminoxane content 10 mg / L) were added under nitrogen protection, and then ethyl acrylate was added, and then propylene and ethylene were introduced. The temperature was raised to 50°C, and the pressure of the reactor was controlled at 0.4MPa. The molar ratio of the first and second monomers was adjusted to 30:70 (wherein the molar ratio of ethylene monomer and ethyl acrylate monomer was equal) by adjusting the added amount of propylene / ethylene / ethyl acrylate. After reacting for 1 hour, the reaction was terminated with acidified ethanol to obtain a propylene-ethylene-ethyl acrylate copolymer. The resulting product was washed 3 times with anhydrous ethanol, filtered, and dried in a vacuum drying oven at 60°C for 4 hours.
[0158] Embodiment 18
[0159] The same procedures as in Example 5 were used except that in <Preparation of polymer> the particle size of the polymer was adjusted to 5 μm and in <Preparation of isolation film containing adhesive layer> the thickness of the first adhesive layer and the second adhesive layer were adjusted to 10 μm respectively.
[0160] Embodiment 19
[0161] The same procedures as in Example 5 were used except that in <Preparation of polymer> the particle size of the polymer was adjusted to 10 μm and in <Preparation of isolation film containing adhesive layer> the thickness of the first adhesive layer and the second adhesive layer were adjusted to 15 μm respectively.
[0162] Embodiment 20
[0163] The present invention is the same as Example 5, except that in <Preparation of an isolation film containing an adhesive layer>, the adhesive layer slurry is uniformly coated on one of the surfaces at the end of a polyethylene (PE) isolation film substrate having a thickness of 9 μm, and in <Preparation of a lithium-ion battery>, one side of the first isolation film containing the first adhesive layer is bonded to the shell.
[0164] Embodiment 21
[0165] Except in the preparation of lithium-ion battery, the second separator extends beyond the end of the second pole piece and does not extend beyond the end of the first pole piece, the first separator is bonded to the shell through the first adhesive layer on the side away from the center of the electrode assembly, and the first separator is bonded to the first current collector through the second adhesive layer on the side facing the center of the electrode assembly, forming a Figure 8 Except for the structure shown, the rest is the same as Example 5.
[0166] Comparative Example 1
[0167] Except that in <Preparation of Isolation Film>, the first adhesive layer is not provided on the surface of the isolation film; and <Preparation of Lithium Ion Battery> is different from Example 1, the rest is the same as Example 1.
[0168] <Preparation of lithium-ion batteries>
[0169] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive and negative electrode sheets to play a role of isolation, and then wound to obtain an electrode assembly to form a Fig.15 The electrode assembly is placed in an aluminum-plastic film packaging bag, and the water is removed at 80°C, and the prepared electrolyte is injected, and the lithium-ion battery is obtained through vacuum packaging, standing, forming, shaping and other processes.
[0170] Comparative Example 2
[0171] Except that in <Preparation of lithium-ion battery>, the area where the first adhesive layer is bonded to the shell is 5% of the contact area between the shell and the electrode assembly, the rest is the same as Example 1.
[0172] Comparative Example 3
[0173] The process was the same as in Example 1 except that the particle size of the polymer was adjusted to 0.5 μm in the step of <Preparation of polymer>.
[0174] Comparative Example 4
[0175] The process is the same as that of Example 1 except that the particle size of the polymer is adjusted to 20 μm in the process of preparing the polymer and the thickness of the first adhesive layer and the second adhesive layer are adjusted to 30 μm in the process of preparing the isolation film.
[0176] The test results of various embodiments and comparative examples are shown in Table 1:
[0177] Table 1
[0178]
[0179]
[0180] It can be seen from Examples 1 to 21 and Comparative Example 1 that the drop test and heavy object impact test results of the lithium ion battery of the present application are better than those of Comparative Example 1, indicating that the lithium ion battery with the isolation membrane of the present application significantly improves its anti-drop performance and anti-heavy object impact performance, reduces the risk of battery failure under special conditions, thereby improving the safety of the lithium ion battery, and has little effect on the energy density of the lithium ion battery.
[0181] The area ratio of the first adhesive layer to the shell is also generally related to the drop resistance and heavy object impact resistance of the lithium-ion battery. It can be seen from Examples 1 to 21 and Comparative Example 2 that as long as the area ratio of the first adhesive layer to the shell is within the scope of the present application, the drop resistance and heavy object impact resistance of the lithium-ion battery can be improved, thereby improving the safety of the lithium-ion battery.
[0182] The particle size of the polymer usually also affects the adhesive properties of the adhesive layer. It can be seen from Examples 1 to 21 and Comparative Examples 3 to 4 that as long as the particle size of the polymer is within the range of the present application, the drop resistance and heavy object impact resistance of the lithium ion battery can be improved, thereby improving the safety of the lithium ion battery.
[0183] It can be seen from Examples 1 to 5 that as the area ratio of the first adhesive layer to the shell increases, the drop resistance and heavy object impact resistance of the lithium-ion battery are improved, especially Example 5, which has the best drop test and heavy object impact test results.
[0184] The content of the high molecular polymer in the adhesive layer usually also affects the adhesive properties of the adhesive layer. It can be seen from Examples 6 to 8 that as long as the content of the high molecular polymer in the adhesive layer is within the scope of the present application, the drop resistance and heavy object impact resistance of the lithium ion battery can be improved, thereby improving the safety of the lithium ion battery.
[0185] The softening temperature and isotacticity of the polymer usually also affect the adhesive properties of the adhesive layer. It can be seen from Examples 9 to 14 that as long as the content of the polymer in the adhesive layer is within the scope of the present application, the drop resistance and heavy object impact resistance of the lithium ion battery can be improved, thereby improving the safety of the lithium ion battery.
[0186] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. An electrochemical device, comprising a housing and a wound electrode assembly disposed in the housing, the electrode assembly comprising a first pole piece and a second pole piece having a polarity opposite to that of the first pole piece, a first separator or a second separator is disposed between the first pole piece and the second pole piece, the first pole piece comprising a first current collector, in, A first adhesive layer is provided on the surface of the first isolation film and / or the second isolation film facing away from the center of the electrode assembly, the first isolation film and / or the second isolation film extends from the tail end of the electrode assembly and is bonded to the shell through the first adhesive layer, and the area where the first adhesive layer is bonded to the shell is greater than or equal to 10% of the contact area between the shell and the electrode assembly.
2. The electrochemical device according to claim 1, wherein: A second adhesive layer is also provided on the surface of the first isolation film and / or the second isolation film facing the center of the electrode assembly. The first isolation film and / or the second isolation film extends from the tail end of the second pole piece and is bonded to the first current collector through the second adhesive layer.
3. The electrochemical device according to claim 1, wherein The surface of the first isolation film away from the center of the electrode assembly faces the surface of the first pole piece toward the center of the electrode assembly, and the surface of the first isolation film toward the center of the electrode assembly faces the surface of the second pole piece away from the center of the electrode assembly.
4. The electrochemical device according to claim 3, wherein: The surface of the second isolation film away from the center of the electrode assembly faces the surface of the second pole piece toward the center of the electrode assembly, and the surface of the second isolation film toward the center of the electrode assembly faces the surface of the first pole piece away from the center of the electrode assembly.
5. The electrochemical device according to claim 1, wherein In a region where the first isolation film or the second isolation film is bonded to the housing, an adhesive force F1 between the first isolation film or the second isolation film and the housing is 5 N / m to 55 N / m.
6. The electrochemical device according to claim 2, wherein: An adhesive force F2 between the first isolation film or the second isolation film and the first current collector is 5.01 N / m to 60 N / m.
7. The electrochemical device according to claim 2, wherein: The adhesion force between the first isolation film and the surface of the first current collector facing away from the center of the electrode assembly is F2, and the adhesion force between the first isolation film and the shell is F1; alternatively, the adhesion force between the second isolation film and the surface of the first current collector facing away from the center of the electrode assembly is F2, and the adhesion force between the second isolation film and the shell is F1, then the difference between F2 and F1 is 1 N / m to 15 N / m.
8. The electrochemical device according to claim 1, wherein Along the winding direction of the electrode assembly, the bonding area between the portion of the first isolation film that exceeds the tail end of the second pole piece and the surface of the first current collector that is away from the center of the electrode assembly is S1, and the bonding area between the portion of the first isolation film that exceeds the tail end of the second pole piece and the shell is S2, and S1 is greater than S2. Alternatively, the bonding area between the portion of the second isolation film that exceeds the tail end of the second pole piece and the surface of the first current collector that is away from the center of the electrode assembly is S1, and the bonding area between the portion of the second isolation film that exceeds the tail end of the first pole piece and the shell is S2, and S1 is greater than S2.
9. The electrochemical device according to claim 1, wherein: Along the winding direction of the electrode assembly, the first isolation film extends from the tail end of the electrode assembly, and the second isolation film exceeds the tail end of the second pole piece and does not exceed the tail end of the first pole piece.
10. The electrochemical device according to claim 1 or 2, wherein: The first adhesive layer and the second adhesive layer include high molecular polymers.
11. The electrochemical device according to claim 10, wherein: The monomers forming the high molecular polymer include a first monomer and a second monomer, the first monomer is propylene, and the second monomer includes at least one of ethylene, vinylidene fluoride, vinyl chloride, butadiene, isoprene, styrene, acrylonitrile, ethylene oxide, propylene oxide, acrylate, vinyl acetate or caprolactone.
12. The electrochemical device according to claim 10, wherein: The high molecular polymer is in the form of particles, and the average particle size of the particles is 1 μm to 10 μm.
13. The electrochemical device according to claim 1 or 2, wherein: The thickness of the first adhesive layer and the second adhesive layer is 1 μm to 50 μm.
14. The electrochemical device according to claim 11, wherein The first monomer accounts for 30 mol % to 95 mol % of the total monomers forming the high molecular polymer, and the second monomer accounts for 5 mol % to 70 mol % of the total monomers forming the high molecular polymer.
15. The electrochemical device according to claim 10, wherein: The polymer satisfies at least one of the following characteristics: (a) the isotacticity of the polymer is 45% to 80%; (b) the softening temperature of the high molecular weight polymer is 130°C to 170°C; (c) The weight average molecular weight of the high molecular weight polymer is 5000 g / mol to 1000000 g / mol.
16. An electronic device comprising the electrochemical device according to any one of claims 1 to 15.
